Nurses’ experiences in caring for people with mental health problems hospitalized due to clinical comorbidities - Gabriella Paulão Previato Piton; Aldair Weber; Ana Paula Rigon Francischetti Garcia; Vanessa Pellegrino Toledo (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to understand nurses’ experiences in caring for people with mental health problems hospitalized due to clinical comorbidities in non-psychiatric Inpatient Units. Methods: qualitative study, guided by Alfred Schutz’s social phenomenology. Sixteen phenomenological interviews were conducted. The content was analyzed and discussed based on the literature, through the composition of three categories of analysis. Results: three categories emerged in the study: Challenges in care faced by nurses; Fragmented care action; and Ideal care. The disarticulation of the clinic was revealed, as described by nurses, showing care as an action far removed from the comprehensiveness of a person. Nurses’ performance is guided predominantly by biomedical reference, disregarding appreciation of subjectivity. Final Considerations: it was observed that nurses attribute the responsibility for patient care to factors external to their life-world, when, in fact, these aspects should be components that help them in comprehensive care construction.